(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article examines the application of differential equations in the digital modeling of processes, with a particular focus on their relevance in economic and technological contexts within Uzbekistan. Differential equations play a vital role in describing dynamic systems across various domains, including finance, production modeling, and resource optimization. With the advancement of computational tools and software, the practical implementation of differential equations has become more accessible and accurate, allowing for the simulation and analysis of complex real-world phenomena. The study highlights the theoretical foundations of differential equations, explores various types commonly used in modeling, and discusses their numerical solutions. The article also emphasizes the importance of integrating mathematical modeling into economic education to enhance students’ analytical and technological skills. This integration fosters more informed decision-making and the ability to engage in predictive analysis using digital tools. By analyzing both the theoretical and practical implications, the article aims to contribute to the development of applied mathematics within the framework of higher education economics programs.